Exploring the Determinants of Behavioral Intention and Use Behavior Toward TikTok Shop Based on the UTAUT2 Model - Rizki Fitriani Muin; Bambang Widjanarko Otok (Parameter: Jurnal Matematika, Statistika dan Terapannya, 2026)
The rapid growth of social commerce through TikTok Shop has opened new opportunities for businesses and consumers in Indonesia, including in the city of Ambon. This study aims to analyze the factors influencing consumers’ behavioral intention and use behavior in shopping on TikTok Shop by applying the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model. The respondents of this research were TikTok Shop users in Ambon who had made at least one transaction, with a minimum sample size of 200 participants. The results show that all UTAUT 2 constructs, except for facilitating conditions on use behavior, have a significant effect on consumers’ intention and usage behavior. The variable behavioral intention was found to be the most dominant factor driving actual usage behavior, with R² values of 0.753 for behavioral intention and 0.817 for use behavior, indicating a strong predictive capability of the model. These findings affirm the relevance of the UTAUT 2 model in explaining technology adoption in the context of social commerce and provide practical implications for platform developers and digital business practitioners to design marketing strategies that align with the characteristics of consumers in eastern Indonesia.